2017
DOI: 10.7150/thno.21471
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Tumor Microenvironment Immune Types across 14 Solid Cancer Types: Immunotherapeutic Implications

Abstract: We performed a comprehensive immuno-genomic analysis of tumor microenvironment immune types (TMITs), which is classified into four groups based on PD-L1+CD8A or PD-L1+cytolytic activity (CYT) expression, across a broad spectrum of solid tumors in order to help identify patients who will benefit from anti- PD-1/PD-L1 therapy. The mRNA sequencing data from The Cancer Genome Atlas (TCGA) of 14 solid cancer types representing 6,685 tumor samples was analyzed. TMIT was classified only for those tumor types that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
171
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(184 citation statements)
references
References 40 publications
9
171
2
2
Order By: Relevance
“…Therefore, high-risk patients were more likely to benefit from immune checkpoint blockade targeting PD-1 and CTLA4. This also accords with the study of Yu-Pei Chen et al 41 their study also suggest that tumors with pre-existing intratumor T cells that express high level of PD-L1 and are suppressed by PD-1/PD-L1 pathway are most likely to benefit from immune checkpoint blockade. Nevertheless, further investigations are needed to evaluate the relationship between the signature and immunotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, high-risk patients were more likely to benefit from immune checkpoint blockade targeting PD-1 and CTLA4. This also accords with the study of Yu-Pei Chen et al 41 their study also suggest that tumors with pre-existing intratumor T cells that express high level of PD-L1 and are suppressed by PD-1/PD-L1 pathway are most likely to benefit from immune checkpoint blockade. Nevertheless, further investigations are needed to evaluate the relationship between the signature and immunotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…Further studies will be needed to determine whether therapeutic drug combinations to manipulate these factors will, in turn, directly impact intratumoral immune cytolytic activity and lead to an immune-mediated anti-tumor effect. Consistent with other studies [7,27,35], we found no association between the non-synonymous TMB and the degree of intratumoral immune cytolytic activity in GBM.…”
Section: Discussionsupporting
confidence: 92%
“…Different lung cancer subtypes have a different biologic background and tissue characteristics . Subsequent genomic analysis indicated that TMIT was associated with mutation and neoantigen numbers in LAC but not in SCC . Based on the IHC analysis, some study reported that PD‐L1 expression was related to a longer or a shorter survival of NSCLC patients, or was even not correlated with their survival .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, according to the expression of PD‐L1 on tumor cells and tumor‐infiltrating lymphocytes (TILs), TMIT classification has been recently proposed by Teng et al, including TMIT I adaptive immune resistance (PD‐L1 positive and high TIL), TMIT II immune ignorance (PD‐L1 negative and low TIL), TMIT III intrinsic induction (PD‐L1 positive and low TIL), and TMIT IV immune tolerance (PD‐L1 negative and high TIL). Several studies based on database analysis have revealed that the proposed classification of TMIT subtypes is important to tailor optimal immunotherapeutic strategies . Nevertheless, the pathological characterizations of TMIT based on both the expression of PD‐L1 on tumor cells and the spatial distribution of TIL especially in LAC and SCC remain unknown.…”
Section: Introductionmentioning
confidence: 99%